The formation way of independent Kazakhstan from the individualism and collectivism perspective - Kabayeva, Zhuldyz; Imanmoldayeva, Bakittizhamal; Mussabaev, Sapargali; Madalieva, Zhanyl; Karanova, Zhanargul (Opción, 2019)
The authors, having applied the phenomenological and comparative approach, set a goal to justify the position about the tendency towards a great predisposition of the Kazakhstani society to collectivism. As a result, it is important to both understand the essence of security and acquire specific knowledge that ensures the strengthening of individual and social security. It is concluded that consideration of the economic, social and political aspects of the formation and development of a young independent state, based on the definition of Kazakh culture as a collectivist culture, will affect the methodology of sociological, political, cultural, economic and philosophical studies